2012
DOI: 10.1016/j.mjafi.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Livedoid vasculopathy managed with hyperbaric oxygen therapy

Abstract: Livedoid vasculopathy Atrophie blanche a b s t r a c tLivedoid vasculopathy is an uncommon condition resulting in painful lower extremity ulceration and scarring. This condition presents as purpuric macules and papules that progress to painful, irregular ulcers of the lower legs and dorsal feet. These ulcerations are often recurrent and chronic with spontaneous remissions and exacerbations that may be seasonal.The first case, a 22-year-old female presented with three-year history of recurrent multiple non-heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…In 2003, Yang et al 4 described two patients with an intractable LV whose ulcers were successfully treated with HBOT. After this, other authors published case reports with similarly satisfactory results in LV patients 5‐11 …”
Section: Hyperbaric Oxygen Therapymentioning
confidence: 88%
See 1 more Smart Citation
“…In 2003, Yang et al 4 described two patients with an intractable LV whose ulcers were successfully treated with HBOT. After this, other authors published case reports with similarly satisfactory results in LV patients 5‐11 …”
Section: Hyperbaric Oxygen Therapymentioning
confidence: 88%
“…After this, other authors published case reports with similarly satisfactory results in LV patients. [5][6][7][8][9][10][11] In February 2020, Zhong et al 12 described the first case report of successful HBOT in a severely ill COVID-19 patient who was failing standard respiratory support (not intubated) and whose disease course was reversed with eight HBOT sessions at 200 kPa over a total treatment time of 95 minutes. Subsequently, Chen et al 13 reported five severe or moderate acute respiratory distress syndrome (ARDS) patients with COVID-19 pneumonia who had been treated under HBOT.…”
Section: Hyperbaric Oxygen Therapymentioning
confidence: 99%
“…Antiplatelets like aspirin, pentoxifylline and dipyridamole remain the first-line therapeutic options along with rivaroxaban, warfarin and low-molecular-weight heparin in associated thrombophilia [ 1 , 5 ] . Second-line therapeutic options include anabolic steroids, intravenous immunoglobulins and hyperbaric oxygen [ 5 , 9 ] . Third-line options in resistant cases include hydroxychloroquine in systemic lupus erythematosus and APLA, oral colchicine or dapsone in vasculitis [ 5 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Some relapses occurred after about six months [58]. In summary, hyperbaric oxygen therapy is time-consuming and expensive, but rapid pain relief and clinical improvement were achieved [59]. Available reports also show that therapeutic success was short-lived in some cases [58,60].…”
Section: Hyperbaric Oxygen Therapymentioning
confidence: 99%